SYSTEMIC HEALTH EFFECTS ASSOCIATED WITH SODIUM ARSENITE EXPOSURE: A REAPPRAISAL - ASHRAF, S; TAHIR, A; AMJAD, A; HAMEED, S; IMTIAZ, R; SHABBIR, A; SHEHZADI, R (Biological and Clinical Sciences Research Journal, 2023)
Sodium Arsenite is a potent toxic mutagenic and xenobiotic metalloid that has been increasing in the environment as a significant pollutant. Contamination of drinking water by chemicals containing arsenic is still a serious public health issue. Prolonged exposure to sodium arsenite can lead to several health problems, including irregularities in the cardiovascular system, diabetes, nephrotoxicity, neurotoxicity, hearing loss, haematological diseases, hepatotoxicity, and infertility. Sodium arsenite is a multi-site carcinogen that can cause cancers in the skin, kidney, colon, lung, and uterus, among other tissues. Numerous research investigations have demonstrated that the toxicity of arsenic is contingent upon various elements such as exposure level, frequency, duration, biological species, age, gender, genetic susceptibilities, and nutritional status. Arsenic exposure has been linked to several consequences, such as apoptosis, cell growth, and alteration of signal transduction pathways. This implies that Arsenite might have incredibly wide impacts rather than targeted effects. Furthermore, several epidemiological studies have documented the exposure sources and the worldwide impacts of arsenic, but the exact method by which it affects various systems, including cancer, is still unknown. More research is needed to give a more precise knowledge of the underlying mechanism.